PRACTICAL ACTIVITIES ALLOW STUDENTS WITH DISABILITIES TO DEVELOP AN UNDERSTANDING OF THEIR ENVIRONMENT AND THEMSELVES - Prudņikova, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The research problem was to find answer to the question: how did the role of practical tasks and activities in the education of students with moderate/severe disabilities is an important one. A review of current and past theories of cognitive development focusing on the role of experiential learning because for today’s students with disabilities there is a stronger emphasis on practical skills and motor skills development opportunities than on traditional learning approaches. Home Economics and Its Technologies is one of the subjects in today’s curriculum where time is allocated to activity-based learning and experiences. Occupational therapy has a positive effect on the child’s psyche, helps to manage and organise the child’s impulses, renews and promotes appropriate work habits, helps organise his/her activities and reduces the child’s focus on his/her own shortcomings or disabilities.